Dreamweaver UltraDev 4 dynamic Web development - Mohler, James L. (Thomson Learning, 2002)
Macromedia's Dreamweaver UltraDev is one of the most essential web development tools on the market. Once developers get a taste of UltraDev's power and productivity, they quickly realize that they can't live without it. Dreamweaver UltraDev 4: Dynamic Web Development, highlighting the very latest feature set, is the ultimate source for learning everything developers need to know about this state-of-the-art web authoring tool. A tutorial-based learning format with step-by-step instruction guides learners through easily performing advanced web development strategies. Highly acclaimed Purdue professor James Mohler and co-author Matt Mooney provide numerous exercises and examples that they have found to be the most valuable for effectively learning UltraDev. The book highlights the use of ASP to create web applications and how to connect to ODBC databases. Without spending extra time telling users what they already know, the book also compares UltraDev to basic Dreamweaver and showcases the new features that comprise the true power of UltraDev.